A Case Report of Synchronous Prostate Cancer and Rectal Gastrointestinal Stromal Tumor and its Management - Watanabe, Ryuta; Ozawa, Akira; Iseda, Tokuhiro; Hatano, Hiroaki (Urology Journal, 2019)
A 72-year-old Japanese man presented to the hospital with complaints of gross hematuria. Contrast enhanced computed tomography revealed a broad-based, approximately 3-cm bladder tumor near the right ureteral orifice and a 5-cm mass located between the prostate and rectum. The patient underwent transurethral resection of the bladder tumor and a transrectal biopsy of the lesion. Histological examination of the specimens suggested that the patient had a muscle invasive adenocarcinoma from transurethral resection and a rectal gastrointestinal stromal tumor in TRUS biopsy. Patient underwent total pelvic exenteration and ileal and colonic stomas to divert urine and faeces. Final pathology report of the resected specimen revealed a rectal gastrointestinal stromal tumor and prostatic adenocarcinoma, which had invaded the urinary bladder and seminal vesicles. Synchronous gastrointestinal stromal tumor in rectum and prostate cancer treated with total pelvic exenteration has not been reported before in literature.